Advertising and Eco-Labels as Influencers of Eco-Consumer Attitudes and Awareness—Case Study of Ecuador - Carrión-Bósquez, N. (2024)
This study examined the impact of green advertising and eco-labels on the attitudes and environmental awareness of millennials purchasing eco-friendly products in shopping centers across Ecuador. The research utilized a quantitative, correlational, cross-sectional methodology with 430 millennials participating. A 20-item survey was administered face-to-face at shopping centers in Quito and Guayaquil, Ecuador. The validity of the research model was established through Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM), employing SPSS 20 and AMOS 24 for statistical evaluations. Findings reveal that green advertising significantly shapes environmental attitudes (β: 0.245) and awareness (β: 0.110), as well as directly influences the purchasing behavior (β: 0.154) towards green products. While eco-labels do not exert a direct effect on purchasing behavior (β: 0.128), they significantly inform attitudes (β: 0.406) and ecological awareness (β: 0.277) of millennials who purchase organic products. This paper is among the pioneering research to delineate the correlation between green advertising elements and the purchasing patterns of green products among millennials in a developing nation. It concludes that marketing strategies centered on green advertising and eco-labels do affect millennials’ attitudes and environmental consciousness, but only advertising has a direct impact on purchasing behaviors, contrary to eco-labels. The research bears social significance as it affirms that millennials are attentive to environmental issues and are actively engaged in promoting sustainability.